Lexical transfer in L2 acquisition and its cognitive categories (a case study of Lithuanian as a foreign language) - Marcinkiewicz, Józef (Scripta Neophilologica Posnaniensia, 2018)
Lexical transfer in L2 acquisition and its cognitive categories (a case study of Lithuanian as a foreign language)